Managing food price inflation in South Asia - Ahmed, Sadiq; Jansen, Hans G. P., 1958-; World Bank. (Dhaka : University Press, 2010)
Contributed articles presented at a seminar.
Copyright: International Bank for Reconstruction and Development/The World Bank.
Includes statistical tables.
Includes bibliographical references and index.
Keywords: Food prices -- Government policy -- South Asia -- Congresses; Food prices -- Government policy -- South Asia -- Statistics -- Congresses; Price regulation -- South Asia -- Congresses; Price regulation -- South Asia -- Statistics -- Congresses; Inflation (Finance) -- South Asia -- Congresses